1975-85 Coal Industry’s Capital Requirements - John F. Frawley (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1975)
This article in all probability will raise some serious doubts as to whether the coal industry-without a national, long-range commitment to coal-can, or should, attempt to meet the capital demands necessary to double coal production in the next 10 years. AMAX Coal, incidentally, doubled its annual coal productive capacity in the past five years from 11 million tons in 1969 to 22 million tons in 1974. Our 1973 annual report stated that we were aiming to triple our 1973 capacity to 50 million tpy by 1978.